1995
DOI: 10.1021/jm00013a012
|View full text |Cite
|
Sign up to set email alerts
|

N-Alkylated Nitrogen-in-the-Ring Sugars: Conformational Basis of Inhibition of Glycosidases and HIV-1 Replication

Abstract: The conformations of nitrogen-in-the-ring sugars and their N-alkyl derivatives were studied from 1H NMR analyses, mainly using 3J(H,H) coupling constants and quantitative NOE experiments. No significant difference was seen in the ring conformation of 1-deoxynojirimycin (1), N-methyl-1-deoxynojirimycin (2), and N-butyl-1-deoxynojirimycin (3). However, it was shown that the C6 OH group in 1 is predominantly equatorial to the piperidine ring, while that in 2 or 3 is predominantly axial, and its N-alkyl group is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 19 publications
1
90
0
Order By: Relevance
“…and seeds of A. pynaertii [5]. Compounds 3 and 11 were identical with N-methyl-DAB and N-methyl-DMJ, which have been chemically synthesized from DAB and DMJ, respectively [10]. From NMR studies, compounds 5, 7, 8 and 9 were identified as new pyrrolidine alkaloids, 1,4-dideoxy-1,4-iminod-xylitol, 2,5-imino-1,2,5-trideoxy-l-glucitol, 2,5-dideoxy-2,5-imino-d-fucitol, and 2,5-imino-1,2,5-trideoxy-d-altritol, respectively.…”
Section: Inhibitorsmentioning
confidence: 99%
“…and seeds of A. pynaertii [5]. Compounds 3 and 11 were identical with N-methyl-DAB and N-methyl-DMJ, which have been chemically synthesized from DAB and DMJ, respectively [10]. From NMR studies, compounds 5, 7, 8 and 9 were identified as new pyrrolidine alkaloids, 1,4-dideoxy-1,4-iminod-xylitol, 2,5-imino-1,2,5-trideoxy-l-glucitol, 2,5-dideoxy-2,5-imino-d-fucitol, and 2,5-imino-1,2,5-trideoxy-d-altritol, respectively.…”
Section: Inhibitorsmentioning
confidence: 99%
“…Mulberry leaf components inhibit the activity of a kind of digestive enzyme for sugar absorption, -glucosidase, and promote slow absorption of glucose into the blood vessels. [1][2][3] The most important substance in mulberry leaves, 1-deoxynojirimycin (1-DNJ), is known to be a strong intestinal -glucosidase inhibitor. Mulberry leaves contain 1-DNJ, 4) so that mulberry leaf products have been commercialized as health foods.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors of ïĄ-glucosidase might reduce the progression of diabetes by decreasing carbohydrate digestion and absorption. In addition, ïĄ-glucosidase inhibition is a promising strategy for the development of novel anti-HIV agents because the glycosylation of viral envelope glycoproteins is essential for viral infectivity [54][55]. The HIV envelope glycoproteins, gp 120 and gp 41, are involved in viral binding and fusion to cells.…”
Section: Chlorogenic Acid Derivatives and Analoguesmentioning
confidence: 99%